2003
DOI: 10.1203/01.pdr.0000090928.93045.be
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Spectroscopy Measurement of Oxygen Extraction Fraction and Cerebral Metabolic Rate of Oxygen in Newborn Piglets

Abstract: Cerebral metabolic rate of oxygen (CMRO 2 ), the rate at which O 2 is consumed in the brain by metabolic processes, is one of the most useful measures of normal brain function. The present study investigated the use of near-infrared spectroscopy (NIRS) in the noninvasive measurement of O 2 extraction fraction (OEF) and CMRO 2 in the newborn piglet. Indomethacin, although used successfully to effect closure of patent ductus arteriosus in the preterm infant, is known to cause transient reductions in cerebral blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
60
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 30 publications
6
60
0
2
Order By: Relevance
“…By combining CBF and absolute Hb concentration measurements, our group has developed an NIRS method for measuring the CMRO 2 that is based on the Fick Principle (Siesjo, 1978). The feasibility of this technique was first shown by measuring the effects of indomethacin on CBF and CMRO 2 in a piglet model (Brown et al, 2003). In agreement with previous studies (Armstead et al, 1988;Coyle et al, 1995), it was shown that indomethacin reduced CBF (by 18%) but had no effect on CMRO 2 .…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…By combining CBF and absolute Hb concentration measurements, our group has developed an NIRS method for measuring the CMRO 2 that is based on the Fick Principle (Siesjo, 1978). The feasibility of this technique was first shown by measuring the effects of indomethacin on CBF and CMRO 2 in a piglet model (Brown et al, 2003). In agreement with previous studies (Armstead et al, 1988;Coyle et al, 1995), it was shown that indomethacin reduced CBF (by 18%) but had no effect on CMRO 2 .…”
Section: Introductionsupporting
confidence: 78%
“…If this variation is real, then it could limit the use of the NIRS technique clinically. However, Brown et al (2003) found only a 15% error in the CMRO 2 when there was a 10% error in the relative contributions of arterial and venous blood.…”
Section: Discussionmentioning
confidence: 80%
“…With regard to the first point, Coyle et al (3) observed in newborn piglets that while CMRO 2 was reduced following administration of a large dose (5.0 mg/kg) of indomethacin, CMRO 2 was not affected by a lower, more clinically relevant dose (0.3 mg/ kg). In a recent study using a novel near-infrared spectroscopy technique to measure CMRO 2 , a dose of 0.2 mg/kg (which is the same dose used in our study) was found to have no effect on CMRO 2 in newborn piglets, although it did reduce CBF and increase oxygen extraction (4). With regard to the second point, prostaglandins are believed to contribute to the regulation of CBF and CMRO 2 in the developing brain, but not in the mature brain (5).…”
supporting
confidence: 43%
“…The method used to calculate CMRO 2 with NIRS has been discussed in detail previously (3). Measurements of CMRO2 were based on the Fick principle:…”
Section: Methodsmentioning
confidence: 99%
“…By combining these measurements, our group has developed a bedside NIRS system capable of rapidly measuring the CMRO 2 that was validated in healthy piglets over a range of metabolic states (3,38). Furthermore, our group observed early, persistent reductions in the CMRO 2 of piglets subjected to transient hypoxia-ischemia (37).…”
mentioning
confidence: 99%